The Ecological Literacy of Prospective Teacher at Sebelas Maret University - Puguh Karyanto; Idhun Prasetyo Riyadi; Baskoro Adi Prayitno (Intelektual Pustaka Media Utama, 2018)
The aim of this study is to determine the ecological literacy ability of prospective teachers at Sebelas Maret University (UNS). This research was conducted on students at the Faculty of Teacher Training and Education (FKIP) UNS Surakarta. The subjects of the study used two courses that gave the ecology course namely Biology Education Study Program and Geography Education Study Program. Subjects in both Study Programs are devoted who are already or are currently receiving ecological subjects. The number of subjects in two study programs were 98 students. Research subjects were taken by stratified random sampling technique. Qualitative descriptive technique is used to analyze each component of ecological literacy. The results showed that the average value of ecological literacy and the value of each component of the students' ecology literacy is still low. Provision of less than optimal ecology concept to be one factor that causes low ecological literacy of student.